Spin-orbit interaction of light induced by transverse spin angular momentum engineering - Zengkai Shao (Nature Portfolio, 2018)
Harnessing both orbital and spin angular momentum in light fields enables various applications in bio-sensing and nano-photonics. Here, the authors create engineered spin-orbit coupling between orbital angular momentum and transverse spin angular momentum in light using a vortex-emitting waveguide.